Effects of extreme drought on soil microbial functional genes involved in carbon and nitrogen cycling in alpine peatland - Yan, Zhongqing; Li, Meng; Hao, Yanbin; Li, Yong; Zhang, Xiaodong; Yan, Liang; Kang, Enze; Wang, Xiaodong; Yang, Ao; Niu, Yuechuan; Yu, Xiaoshun; Kang, Xiaoming; et al. (Frontiers in Ecology and Evolution, 2023)
Diverse microorganisms drive biogeochemical cycles and consequently influence ecosystem-level processes in alpine peatlands, which are vulnerable to extreme drought induced by climate change. However, there are few reports about the effects of extreme drought on microbial function. Here we identify microbial functional genes associated with carbon and nitrogen metabolisms of extreme drought experiments that occurred at different periods of plant growth, the results show that early extreme drought reduces the abundance of functional genes involved in the decomposition of starch and cellulose; midterm extreme drought increases the abundance of lignin decomposition functional genes; late extreme drought reduces the hemicellulose but increases cellulose decomposition functional genes. In the carbon fixation pathway, extreme drought mainly changes the abundance of functional genes involved in the reductive citrate cycle process, the 3-hydroxy propionate bi-cycle, the dicarboxylate-hydroxybutyrate cycle and the incomplete reductive citrate cycle. Among the nitrogen cycling functional genes, amoA involved in oxidizing ammonia to hydroxylamine significantly increases under early extreme drought; midterm extreme drought reduces nrtC and nifD genes, which participate in nitrate assimilation and nitrogen fixation, respectively; late extreme drought significantly increases hcp genes involved in ammonification. pH and TN had the largest effects on the carbon degradation, fixation and nitrogen cycling functional genes. The composition of microbial community structures involved in carbon fixation differed between treatments in early extreme drought. There is a good linear fit between the diversity of gene abundance and corresponding microbial communities in the reductive citrate cycle, hydroxy propionate-hydroxybutyrate cycle, dicarboxylate-hydroxybutyrate cycle and nitrogen cycling, which suggests that the functional genes and community composition of microorganisms involved in these processes are consistent in response to extreme drought. This study provides new insights into the adaptability and response characteristics of microbial communities and functional genes in plateau peatland ecosystems to extreme drought events.